2020
DOI: 10.1177/0748233720967531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium on the viability on monolayer cultures of synoviocytes, chondrocytes, and Hoffa: A preliminary study

Abstract: Osteoarthritis (OA) is the gradual loss of articular cartilage and involves several tissues, such as the synovial membrane, meniscus, ligaments, and adipose tissue known as Hoffa fat pad. There are largely unexplored factors that lead to OA development, such as the impact of exposure to heavy metals like cadmium (Cd) on the viability of cells in the knee joint tissue. The objective of this report was to identify the cell type with the highest susceptibility to Cd toxicity with respect to cell viability and dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…10 A recent study showed that Cd chloride can significantly decrease the viability of synovial cells and chondrocytes. 11 Mechanistic studies suggest that Cd exposure may be a risk factor for the development of OA by interfering with the absorption of other elements necessary for cartilage homeostasis and triggering oxidative stress. 12 However, other studies have found that injection of low-dose Cd into the joints of rats ameliorates arthritis, reduces clinical scores, and protects against bone/cartilage injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 A recent study showed that Cd chloride can significantly decrease the viability of synovial cells and chondrocytes. 11 Mechanistic studies suggest that Cd exposure may be a risk factor for the development of OA by interfering with the absorption of other elements necessary for cartilage homeostasis and triggering oxidative stress. 12 However, other studies have found that injection of low-dose Cd into the joints of rats ameliorates arthritis, reduces clinical scores, and protects against bone/cartilage injury.…”
mentioning
confidence: 99%
“…Lanocha-Arendarczyk et al found that the Cd concentration in the tibia of OA patients was higher and was proportional to the amount of smoking 10 . A recent study showed that Cd chloride can significantly decrease the viability of synovial cells and chondrocytes 11 . Mechanistic studies suggest that Cd exposure may be a risk factor for the development of OA by interfering with the absorption of other elements necessary for cartilage homeostasis and triggering oxidative stress 12 .…”
mentioning
confidence: 99%